Creative capital in production, inefficiency, and inequality: A theoretical analysis - Amit Batabyal; Peter Nijkamp (European Regional Science Association (ERSA), 2016)
We analyze inefficiency and inequality associated with the use of creative capital to produce a final good in a regional economy. Specifically, we first study a case in which the individual creative capital units are perfect substitutes in the production of the final good. We show that the equilibrium outcome is inefficient and that there is too little application of effort. Second, we define an indicator of inequality and show that an increase in inequality enhances efficiency and that it is, in principle, possible to achieve complete efficiency. Third, we focus on the case where the individual creative capital units are perfect complements and show that the equilibrium outcome is, once again, inefficient with too little effort application. Finally, we contend that our theoretical results provide a possible rationale for the observed income inequality in cities and regions in which the activities of the creative class constitute a large part of all economic activities.
Keywords: R11; D20; 330; Creative Capital; Inefficiency; Inequality